Table of Content - - (Journal of engineering sciences and information technology, 2023)
Table of Content 1. The impact of recruitment of materials to improve energy efficiency in buildings Co-Prof. Rubaia Ali Bin Ali, Co-Prof. Fahd Saleh Gohar, Amr Rubaia Mukaydekh 2. Space Recycle between Theory and practice - Case study: Ministries Square, Down Town Eng. Maya Atef Bendary 3. A Theoretical Comparative Review of Computer-Aided Landscape Design Tools: Features, Benefits, and Limitations Eng. Sami Abdullah Mandani, Eng. Abdullah Ebrahim Aljasem 4. Analysis of the Lost Circulation process for the development of drilling operations in Al-Omar oil field – Syria Eng. Tareq Ali Farid 5. The Role of Artificial Intelligence in Civil Engineering Applications and Programs Eng. Mohsen Saud Alghurair , Ayman Rushdy Fahim